Analisis Unsur Intrinsik Dan Nilai Moral Pada Cerpen “Pispot” Karya Hamsad Rangkuti - Puja Sri Rahayu; Salwa Rachmadini (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The short story "Pispot" by Hamsad Rangkuti is one of Indonesian literary works that sharply describes the social reality of society. Through heartbreaking stories, Hamsad Rangkuti highlights the problems of injustice and abuse of power that often arise in everyday life. This research aims to analyze the intrinsic elements in the short story "Pispot" in depth and explore the moral values ​​contained in it. This analysis can provide a deeper understanding of Hamsad Rangkuti's literary works and their relevance in today's social context. This research found that the short story "Pispot" effectively depicts social injustice through contrasting characters, a thrilling plot, and a gloomy background. The main moral values ​​in this short story include justice, honesty and humanity. This short story also voices criticism of an unfair legal system and abuse of power.